Sacral neuromodulation in patients with neurogenic lower urinary tract dysfunction - Cecile T. Pham; Cameron J. Parkin; James Kovacic; Siying Yeow; Yunzhi Yang; Danielle Delaney; Amanda Chung (Current Urology)
Abstract. Background. Limited published data exist regarding the utility of sacral neuromodulation (SNM) for neurogenic lower urinary tract dysfunction (NLUTD), consisting of only small case series, and, to our knowledge, no Australian data have been published. The aim of this study was to evaluate the clinical outcomes of SNM for treatment of NLUTD in Australian patients. Methods. A retrospective analysis was conducted of patients who received a permanent SNM implant between December 2014 and March 2021. Patients completed a urodynamic test preoperatively. They completed a 3-day bladder diary, uroflowmetry, and postvoid residual measurement preoperatively and at 6-month intervals postoperatively following SNM insertion. Urinary function, patient-reported outcome measures, and adverse events were assessed. Results. A total of 36 patients received a permanent SNM implant. The mean duration of follow-up was 25 ± 20 months, with the majority (89%, n = 32) of patients reporting a >50% improvement on bladder diary evaluation. There was a significant increase in void volume (p < 0.001), decrease in postvoid residual (p < 0.001), decrease in voiding frequency (p < 0.001), decrease in incontinence episodes (p = 0.002), and decrease in pad number (p < 0.001). There was no significant difference in peak flow (p = 0.21). There was no significant difference in SNM efficacy between patients with progressive or nonprogressive neurological conditions. Conclusions. Sacral neuromodulation is a safe and effective therapy for NLUTD in the context of both progressive and nonprogressive neurological conditions. It should be offered more readily to patients with NLUTD as a minimally invasive treatment option with the potential to make clinically meaningful improvements in quality of life.